Genidentyczność a metafizyka persystencji: endurantyzm, perdurantyzm i eksdurantyzm - Grygianiec, Mariusz (Filozofia Nauki, 2005)
The metaphysical explanations of genidentity are very important both for scien-tific researches and for everyday human activities. Endurantism, perdurantism and exdurantism (stage view and point-eventism) are the standard metaphysical theo-ries, which provide descriptions and explanations of relations of change and persistence. The descriptions and explanations in question give simultaneously the truth-conditions for statements about an identity of objects, which persist and undergo changes in time. The main aim of the paper is to formulate the above-mentioned metaphysical stances and to give the general account of the relation of genidentity within a conceptual framework of these theories. The second aim is to provide a suitable reconstruction of criteria of genidentity, which are appropriate for the three metaphysical doctrines.